Nilai Moral Dalam Novel” Rasina” Karya Iksaka Banu - Sintia; Yeni Ernawati (Journal of Mandalika Literature, 2024)
The problems raised in this research discuss the forms of moral values ​​contained in the novel Rasina by Iksaka Banu.morals are the teaching of good and bad actions and behavior of a person. Literary work is a work that is very closely related to the real life of humans themselves, an author expresses or the media used to appreciate the results of his thoughts can be through written media such as novels, poetry, short stories and many more. A novel is a form of literary work that presents various life problems in the form of a narrative or storyline. Apart from that, the novel also has supporting elements in it, namely intrinsic elements and extrinsic elements which have been neatly arranged. In a novel, apart from containing a storyline in the form of a narrative, there are also various values ​​that can be learned in everyday life. The novel also contains various problems and conflicts in it. This is what makes the novel a literary work that attracts a lot of attention from readers or literature lovers.The results of the research are Caring for Others, Helping Each Other, Deliberation, Living in Harmony, Forgiving, Keeping Promises, Respecting Others.